2014
DOI: 10.1111/brv.12089
|View full text |Cite
|
Sign up to set email alerts
|

The behavioural and physiological strategies of bird and reptile embryos in response to unpredictable variation in nest temperature

Abstract: Temperature profoundly affects the rate and trajectory of embryonic development, and thermal extremes can be fatal. In viviparous species, maternal behaviour and physiology can buffer the embryo from thermal fluctuations; but in oviparous animals (like most reptiles and all birds), an embryo is likely to encounter unpredictable periods when incubation temperatures are unfavourable. Thus, we might expect natural selection to have favoured traits that enable embryos to maintain development despite those fluctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 134 publications
2
89
1
Order By: Relevance
“…Unfortunately, these early stages are when development is most thermally sensitive (Yntema 1968;Shine and Elphick 2001;Birchard 2004), and embryos could most affect their fitness by thermoregulating. Still, thermoregulation in the latter two-thirds of development could provide some benefit, such as increasing the rate of development, allowing heat-stress avoidance, and potentially adjusting offspring sex (Georges et al 2005;Janzen 2008;Du and Shine 2015). However, as embryos enter later stages of development, they grow rapidly and quickly fill the majority of the egg's space (Andrews 2004).…”
Section: E22 the American Naturalistmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, these early stages are when development is most thermally sensitive (Yntema 1968;Shine and Elphick 2001;Birchard 2004), and embryos could most affect their fitness by thermoregulating. Still, thermoregulation in the latter two-thirds of development could provide some benefit, such as increasing the rate of development, allowing heat-stress avoidance, and potentially adjusting offspring sex (Georges et al 2005;Janzen 2008;Du and Shine 2015). However, as embryos enter later stages of development, they grow rapidly and quickly fill the majority of the egg's space (Andrews 2004).…”
Section: E22 the American Naturalistmentioning
confidence: 99%
“…Recent work, however, has demonstrated that the embryos of many amniotes-including species of turtle, crocodile, snake, and bird-adjust their positions within the egg in response to thermal gradients, actively moving toward or away from external heat sources (Du et al 2011;Zhao et al 2013;Li et al 2014). Such observations of embryonic thermal taxis raise the possibility that vertebrate ectotherm embryos behaviorally thermoregulate similar to posthatching individuals (Du et al 2011;Du and Shine 2015). Minor changes in temperature (e.g., of 17C-27C) can have dramatic impacts on reptile development, affecting everything from embryonic survivorship to incubation duration to offspring phenotype (e.g., body size and shape, performance, and sex in some species; reviewed in Janzen and Paukstis 1991;Birchard 2004;Vitt and Caldwell 2009;Andrews and Schwarzkopf 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lizards face different thermal stresses during the life cycle, because embryos develop in a confined space while adults enjoy freedom and mobility. Consequently, embryo temperatures conform to changes in soil temperature [22], while adults thermoregulate with great precision [23]. Mothers deposit their embryos in shallow nests, where they experience fluctuating and unpredictable temperatures for more than two months [24].…”
Section: Introductionmentioning
confidence: 99%
“…1B). We suspect that the extended exposure to higher temperatures was also associated with longer periods of elevated metabolic rates (Gatten, 1974;Du and Shine, 2015;Sun et al, 2015). Recently, Sun et al (2015) reported that increasing incubation temperatures are associated with significant increases in the rate of aerobic respiration and the activity of cytochrome oxidase (involved in the electron transport chain) in reptile embryos.…”
Section: Discussionmentioning
confidence: 99%